Pendidikan Kesehatan Remaja Putri Luar Sekolah Tentang Cara Mengatasi Dismennorhoe (Nyeri Haid) di Kelurahan Fatubenao - Kabupaten Belu - Provinsi NTT: Pendidikan Kesehatan Remaja Putri Luar Sekolah Tentang Cara Mengatasi Dismennorhoe (Nyeri Haid) - Maria Beata Aku; Eti Salafas; Yosefina Lin; Etilia Abuk (Universitas Ngudi Waluyo, 2022)
Abstract Reproductive health is an important issue for adolescents. One of the initial changes that occur in adolescents is menstruation, which can cause dysmenorrhea. Dysmenorrhea can interfere with learning activities and can also indirectly affect the productivity and quality of life of adolescents. In Indonesia, the incidence of dysmenorrhea reaches 60-70% with a prevalence of 64.5% at the age of 17-24 years. The incidence of primary dysmenorrhea in Indonesia is 54.89%, while the remaining 45.11% is secondary. One way to reduce menstrual pain is yoga, the benefits of yoga include increasing blood circulation throughout the body, lung capacity when breathing, reducing body, mind and mental tension, and reducing pain. In addition, yoga is also believed to reduce fluid that accumulates in the waist which causes pain during menstruation. The purpose of this Community Service is to increase knowledge of young women about dysmenorrhea and how to reduce dysmenorrhea complaints with Yoga in the Fatubenao Belu Village, East Nusa Tenggara. The method is carried out by providing health education to young women and teaching yoga exercises. The average pre-test result for female youth is 58.69 with a minimum score of 34.33 and a maximum of 83). The average post-test result of knowledge of young women is 75 with a minimum score of 48 and a maximum of 95. With increased knowledge, young women are expected to be able to do yoga exercises to deal with menstrual pain at home, and be able to apply the knowledge gained as knowledge about women's reproductive health through yoga